1984
DOI: 10.1111/j.1471-4159.1984.tb02779.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of the Effects of Neurotransmitters on the Na+,K+‐ATPase System

Abstract: The aim of the present experiments was to study the effects of the neurotransmitters acetylcholine, noradrenaline, 5-hydroxytryptamine, and dopamine on the Na+,K+-ATPase of rat brain synaptosomal fractions. It is shown that dopamine at low concentrations specifically inhibits the Na+,K+-ATPase of synaptic membranes from the brain regions rich in dopaminergic endings, but has no effect on the synaptosomal Na+,K+-ATPase from the other parts of brain. Acetylcholine and noradrenaline have similar specific effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…In accordance with the data reported (Robinson and Flasher 1979; Kometiani et al 1984), the presence of only one catalytic site per α-subunit has been identified for the Na, K-ATPase system. Therefore, the molecule has a dimeric nature with two identical subunits, 2(αβ), that must be a universal system for all P-type transport ATPases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with the data reported (Robinson and Flasher 1979; Kometiani et al 1984), the presence of only one catalytic site per α-subunit has been identified for the Na, K-ATPase system. Therefore, the molecule has a dimeric nature with two identical subunits, 2(αβ), that must be a universal system for all P-type transport ATPases.…”
Section: Discussionsupporting
confidence: 90%
“…In the Cl-ATPase study we applied kinetic analysis of multisited enzyme systems (Kometiani et al 1984), which is a single method used from kinetic investigation of multisited enzyme systems.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, Kometiani et al (1984) have reported inhibition of the Na +/K+-ATPase by acetylcholine only in cholinergic synaptosomal membranes. No effect of ace@choline on Na+/K÷-ATPase was seen in membranes from liver, kidney, red cell ghosts and adrenergic synaptosomes.…”
Section: Discussionmentioning
confidence: 99%
“…There arise many questions and one of them is the problem of participation of Ca 2+ ions [ 5 , 6 ]. Ca 2+ ion and EGTA are modifiers of the Na/K-ATPase system and at the same time EGTA sharply attenuates the inhibition of Na/K-ATPase by NA [ 2 ]. Therefore arises a necessity to clarify the role of Ca 2+ ions in the mechanism of action of NA and SF on the Na/K-ATPase system.…”
Section: Introductionmentioning
confidence: 99%